Identifying New Drug Targets for Potent Phospholipase D Inhibitors: Combining Sequence Alignment, Molecular Docking, and Enzyme Activity/Binding Assays. (29th January 2016) - Djakpa, Helene; Kulkarni, Aditya; Barrows‐Murphy, Scheneque; Miller, Greg; Zhou, Weihong; Cho, Hyejin; Török, Béla; Stieglitz, Kimberly
Abstract : Phospholipase D enzymes cleave phospholipid substrates generating choline and phosphatidic acid. Phospholipase D from Streptomyces chromofuscus is a non‐HKD (histidine, lysine, and aspartic acid) phospholipase D as the enzyme is more similar to members of the diverse family of metallo‐phosphodiesterase/phosphatase enzymes than phospholipase D enzymes with active site HKD repeats. A highly efficient library of phospholipase D inhibitors based on 1, 3‐disubstituted‐4‐amino‐pyrazolopyrimidine core structure was utilized to evaluate the inhibition of purified S. chromofuscus phospholipase D. The molecules exhibited inhibition of phospholipase D activity (IC50 ) in the nanomolar range with monomeric substrate diC4 PC and micromolar range with phospholipid micelles and vesicles. Binding studies with vesicle substrate and phospholipase D strongly indicate that these inhibitors directly block enzyme vesicle binding. Following these compelling results as a starting point, sequence searches and alignments with S. chromofuscus phospholipase D have identified potential new drug targets. Using AutoDock, inhibitors were docked into the enzymes selected from sequence searches and alignments (when 3D co‐ordinates were available) and results analyzed to develop next‐generation inhibitors for new targets. In vitro enzyme activity assays with several human phosphatases demonstrated that the predictive protocol was accurate. The strategy of combining sequence comparison, docking, and high‐throughput screening assays has helped to identify new drug targets and provided some insight into how to make potential inhibitors more specific to desired targets. Abstract : Phospholipase D inhibitors based on 1, 3‐disubstituted‐4‐amino‐pyrazolopyrimidine core structure were utilized to evaluate inhibition of purified S.chromofuscus phospholipase D. Phospholipase D inhibition (IC50 ) was in the nanomolar range. Sequence searches/alignments with S.chromofuscus phospholipase D identified potential new drug targets. Inhibitors were docked into the selected enzymes and results analyzed to develop next generation inhibitors for several human phosphatases. In vitro assays demonstrated that the predictive protocol was accurate. The strategy of combining sequence comparison, docking, and high through‐put screening assays identified new drug targets.